Poster Presentations 2017
DOI: 10.1136/bmjspcare-2017-00133.90
|View full text |Cite
|
Sign up to set email alerts
|

P-91 Integration of specialist palliative care into a tertiary non-malignant service: evaluation of potential geographical disparity

Abstract: Participants described the transition period as a difficult time for both the YP and their families, with a perceived lack of adult services available for them. All groups agreed that the pilot project had a positive impact on the YP and their families, with the social benefits highlighted as a key factor. All participants were keen for the project to continue, ideally on a more frequent basis with more overnight stays, and the parents were keen to be more involved in the running of the service. Conclusion The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…25 These results imply a geographical disparity in access to palliative care, which has also been identified in previous work by the North East and Cumbria interstitial lung disease service. 39,40 Variability in access to specialist palliative care services is also known to be an issue for patients with other chronic respiratory diseases. 41 Referral to palliative care services is likely to be influenced by healthcare professionals' familiarity with local services and whether specialist services exist.…”
Section: Comparison With Other Workmentioning
confidence: 99%
“…25 These results imply a geographical disparity in access to palliative care, which has also been identified in previous work by the North East and Cumbria interstitial lung disease service. 39,40 Variability in access to specialist palliative care services is also known to be an issue for patients with other chronic respiratory diseases. 41 Referral to palliative care services is likely to be influenced by healthcare professionals' familiarity with local services and whether specialist services exist.…”
Section: Comparison With Other Workmentioning
confidence: 99%
“…The described service structure barriers to advance care planning described are not unique and have previously been reported by other tertiary regional services. 1921 A lack of clarity and information sharing is described. Regional and local services need clear understanding of each other’s working practices.…”
Section: Discussionmentioning
confidence: 99%
“…Regional and local services need clear understanding of each other's working practices. 19,20 Agreements regarding responsibility and communication may facilitate good advance care planning and palliative care. Indicators of deterioration, such as frequent admissions, should be highlighted to regional and local teams.…”
Section: Servicementioning
confidence: 99%
“…Connie Swenson, 2 John MacArtney, 3 Rachel Perry, 4 Lucy Hetherington, 5 Lisa Graham-Wisener, 6 Hazel Lamberton, 4 Emma Carduff, 7 Scott Murray, 8 Anne Finucane. 1 Background Understanding complex need as the defining characteristic of episodes requiring specialist palliative care (SPC) is key to hospice service development.…”
Section: The Nature Of Complex Need In Specialist Palliative Care Referralsmentioning
confidence: 99%
“…In January 2016 specialist palliative care (SPC) support was embedded in a regional IPF clinic. Initial service review (Kavanagh, 2017) suggested potential geographical disparities in access to both anti fibrotics and clinic-based SPC. Aim To repeat the 2016 review to assess whether geographical disparities have changed over time.…”
Section: The Nature Of Complex Need In Specialist Palliative Care Referralsmentioning
confidence: 99%